Vibration behaviour of pre-stressed precast hollow core floor with concrete topping thickness and boundary condition - Rahimi, Muhammad Imran (2020)
In the current design, the usage of lightweight and long-span precast, which is renowned in construction, is prone to the floor serviceability issue, especially in floor vibration. The pre-stressed precast hollow core floor (PPHCF) in a four-storey office building was selected in performing an investigation on floor vibration regarding its properties. The PPHCF is known for its long-span and had longitudinal void along the length, which is made similar to lightweight concrete floor properties. These properties are prone to the floor vibration issue, which are also influenced by its mass and stiffness. The preliminary study on prediction analysis is performed to determine a testing location. Two-floor areas (Area A and Area B) was selected, and a modal vibration analysis was compared from experimental modal analysis (EMA) and Finite Element Analysis (FEA) by using SAP2000 software package. In both analyses, natural floor frequency was found lower than 10Hz, and a correlation between the EMA and FEA is accepted. Thus, the floor was categorised as a low-frequency floor based on floor concrete material limitation. This thesis focused on vibration effects in tackling the low natural frequency with different topping thickness and boundary condition by the parametric study in observing its vibration behaviour pattern. The main issue in the actual design was the boundary condition between the PPHCF and l-beam, which precast is rested on l-beam without any connection to it. This parametric study discussed the mass and stiffness domination effect in different topping thickness and the stiffness effect on each assigned boundary condition. Thus from the parametric study, the boundary condition is more influenced in floor vibration rather than concrete topping thickness.